The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1121/1.5132950
|View full text |Cite
|
Sign up to set email alerts
|

The chinchilla animal model for hearing science and noise-induced hearing loss

Abstract: The chinchilla animal model for noise-induced hearing loss has an extensive history spanning more than 50 years. Many behavioral, anatomical, and physiological characteristics of the chinchilla make it a valuable animal model for hearing science. These include similarities with human hearing frequency and intensity sensitivity, the ability to be trained behaviorally with acoustic stimuli relevant to human hearing, a docile nature that allows many physiological measures to be made in an awake state, physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 214 publications
1
23
0
1
Order By: Relevance
“…The results from chinchilla studies ( Harding & Bohne 2009 ) showed that 4-kHz octave band of noise could produce greater NIPTS especially for outer hair cell damage than 0.5 kHz octave band of noise, suggesting the chinchilla cochlea is more sensitive to high-frequency noise, especially at 4 kHz. The chinchilla animal model supports the results shown in Figure 3 because the chinchilla’s auditory system is very similar to that of humans ( Trevino et al 2019 ). Moreover, it can be seen from Figures 3 B and C that the hearing loss notch degree at the high frequencies (3 to 6 kHz) deepens with the increase of L Aeq and kurtosis, and reaches the maximum at 4 kHz.…”
Section: Discussionsupporting
confidence: 78%
“…The results from chinchilla studies ( Harding & Bohne 2009 ) showed that 4-kHz octave band of noise could produce greater NIPTS especially for outer hair cell damage than 0.5 kHz octave band of noise, suggesting the chinchilla cochlea is more sensitive to high-frequency noise, especially at 4 kHz. The chinchilla animal model supports the results shown in Figure 3 because the chinchilla’s auditory system is very similar to that of humans ( Trevino et al 2019 ). Moreover, it can be seen from Figures 3 B and C that the hearing loss notch degree at the high frequencies (3 to 6 kHz) deepens with the increase of L Aeq and kurtosis, and reaches the maximum at 4 kHz.…”
Section: Discussionsupporting
confidence: 78%
“…This gap can be addressed by extending acoustic SI models to the neural spike-train domain. In particular, spike-train data obtained from preclinical animal models of sensorineural hearing loss can be used to explore the neural correlates of perceptual deficits faced by hearing-impaired listeners [ 78 ]. These insights will be crucial for developing accurate SI models for hearing-impaired listeners.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exotic species can serve as important models for human diseases. Examples are the armadillo Dasypus novemcinctus for research on leprosy [97], the turtle Trachemys scripta to study brain hypoxia and anoxia [98], and the pet Chinchilla lanigera to investigate hearing loss [99]. Diurnal rodents represent unique models of cone-related retinal diseases [100].…”
Section: The Use Of Experimental Models In Biomedicinementioning
confidence: 99%